Added Value Improvement on Arabica Coffee Wet Process MethodUsing Model Kemitraan Bermediasi (Motramed) on Unit Pengolahan Hasil at Ngada Residence - NTT - Djoko Soemarno; Surip Mawardi; Maspur Maspur; Henik Prayuginingsih (Indonesian Coffee and Cocoa Research Institute, 2009)
Ngada Residence is main producen region Arabica coffee in Nusa Tenggara Timur province. There are scattered on district of Bajawa and Golewa, that all of them effort by farmers and low quality, so farmers get low price and coffee development slowly than other coffee region in Indonesia. But, on the other hand, Arabica coffee from this region have potential special taste to be export quality coffee beans. One of way to solve to develop this quality is implementation coffee processing by Wet Process methode and support marketing system better by Model Kemitraan Bermediasi (Motramed). This research started from June until October 2007 at two centre district of Arabica coffee, there are district Bajawa are UPH Fa Masa on Beiwali village, UPH Wonga Wali on Susu village, UPH Papa Taki on Bomari village, UPH Suka Maju on Ubedolumolo village and Kecamatan Golewa are UPH Papa Wiu on Mangulewa village, UPH Meza Mogo on Rakateda II village and UPH Ate Riji on Were I village. This research want to know added value, cost efficiency, and profit on Arabica coffee processing used wet process methode on Unit Pengolahan Hasil (UPH) at Ngada Residence. Data was analysed by approximation added value, R-C Ratio analisys and t-One Sample Test. The result showed that Arabica coffee wet process could improved phisic and taste quality, lower of beans size, higher quality grade, smaller defect beans, moisture content lower, had special taste and very few taste defect. Those quality improvement improved price market to be higher, the added value about Rp4,390,- per kg and improved profit for farmers.Key words : Arabica coffee, wet process, quality, added value, efisiency, revenue.